Speech by Mr. Alban Sandi Bonilla, Dean, Faculty of Arts at the Inauguration of Professional Lecture "Managing Information in Specialized Areas in Costa Rican - Bonilla Sandí, Albán (1992)
In the inauguration of the cycle of Professional conferences the Dean of the Faculty of Philosophy and Letters is pronounced with the speech "The Handling of the Information in Specialized Airplanes in Costa Rica".